Southern frontier humor : new approaches - Piacentino, Edward J., 1945- (University Press of Mississippi, 2013)
Since its inception in the early 1830s, southern frontier humor (also known as the humor of the Old Southwest) has had enduring appeal. The onset of the new millennium precipitated an impressive rejuvenation of scholarly interest. Beyond Southern Frontier Humor: Prospects and Possibilities represents the next step in this revival, providing a series of essays with fresh perspectives and contexts. First the book shows the importance of Henry Junius Nott, a writer virtually unknown and forgotten who mined many of the principal subjects, themes, tropes, and character types associate.